KELAYAKAN PENYEDIAAN INFRASTRUKTUR AIR BERSIH KAWASAN PESISIR BERDASARKAN PERSEPSI MASYARAKAT (KECAMATAN TELUK BETUNG TIMUR, KOTA BANDAR LAMPUNG) - Eva Valen Erimta Ginting; Lutfi Setianingrum; Tetty Harahap (Jurnal Perencanaan dan Pengembangan Kebijakan, 2023)
Water is essential for the activities and maintenance of human life, such as meeting daily household needs. Clean water is an integral part of who gets priority in urban planning. The importance of clean water for human life, clean water infrastructure required management well and deserved. Directorate General of Human Settlements, PUPR (2007), explains Bandar Lampung City uses PDAM Way Rilau as a pipe network for clean water services. One area of ​​Bandar Lampung City experiencing clean water problems is the Teluk Betung Timur Coastal Area. The issue of providing clean water infrastructure in coastal areas is the quantity of clean water infrastructure, distribution of clean water, and clean water quality consisting of clean water quantity, continuity, and physical quality. This research aims to review the feasibility of providing clean water infrastructure in coastal areas based on the public perception in Teluk Betung Timur District. This research used the descriptive analysis method to explain existing conditions and monitor the feasibility of providing infrastructure clean water in the research areas. After that needs to be calculated is used with the methods weighting to judge the feasibility of delivering clean water infrastructure in coastal areas of Teluk Betung Timur District. Based on the analysis results, the provision of infrastructure clean water in coastal areas of the Teluk Betung Timur District. They are still lacking worth. This inadequacy is identified in the quantity of clean water infrastructure, distribution, and quality of clear water.